Are in Person and Telephone Interviews Equivalent Modes of Administrating the CAT, the FACIT-FS and the SGRQ in People With COPD? - Rocha, Vânia; Jácome, Cristina; Martins, Vitória; Marques, Alda (Frontiers in Rehabilitation Sciences, 2021)
Background: The COVID-19 pandemic brought numerous challenges, namely in routine assessment of people with chronic obstructive pulmonary disease (COPD). The COPD Assessment Test (CAT), the Functional Assessment of Chronic Illness-Fatigue-Subscale (FACIT-FS) and the St. George's respiratory questionnaire (SGRQ) are important patient-reported outcome measures used to assess people with COPD, but its face-to-face application has been compromised. The telephone interview offers a simple and effective alternative, yet uncertainty regarding its equivalence remains. This study aimed to establish the reliability and validity of the CAT, the FACIT-FS and the SGRQ administered by telephone interview in people with COPD. Methods: Data from an observational prospective study including people with COPD were analyzed. Participants answered to the CAT, FACIT-FS and SGRQ questionnaires in person and by telephone, with a maximum interval of 48-h. Participants were randomly selected to answer first to the in-person questionnaire followed by telephone or vice versa. Reliability measures included internal consistency with Cronbach's alpha, test-retest reliability with the intraclass correlation coefficient (ICC2,1), test-retest measurement error with the standard error of measurement (SEM) and agreement with the Bland and Altman 95% limits of agreement. Validity was assessed with the Spearman correlation (rho). Results: Fifty-five people with COPD (44 men; 68.1 ± 7.9 years; FEV1: 59.1 ± 20.3% predicted) were included. Similar internal consistency was observed between in person vs. telephone interview for the CAT (0.82 vs. 0.84), the FACIT-FS (0.83 vs. 0.84) and the SGRQ (0.92 vs. 0.93). Test-retest reliability was excellent, with an ICC2,1 of 0.77 (95% CI: 0.65; 0.86), 0.86 (95% CI: 0.77; 0.92) and 0.94 (95% CI: 0.90; 0.96) for the CAT, FACIT-FS and SGRQ total scores, respectively. The SEM showed a low level of associated measurement error and the Bland and Altman plots illustrated a good level of agreement between both modes of administration, with no evidence of systematic bias. Robust positive correlations (rho 0.87–0.94, p < 0.001) were found for the CAT, FACIT-FS and SGRQ total scores applied by both methods. Conclusion: The telephonic administration of the CAT, the FACIT-FS and the SGRQ are a valid and reliable alternative approach to in person interviews for monitoring symptoms and health-related quality of life in people with COPD. The telephone might be an important add-on for personalized assessment and management of COPD thru remote monitoring.